QUARTER LIFE CRISIS TERHADAP MAHASISWA STUDI KASUS DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS PGRI MAHADEWA INDONESIA - I Putu Karpika; Ni Wayan Widiyani Segel (Widyadari : Jurnal Pendidikan, 2021)
The stages of human development have their respective complex problems. A person's maturity develops over time and becomes a necessity for individuals to pass the transition process. This often leads to crises and problems within the individual. Yudrik Yahja (2011) in his book entitled Psikologi Perkembangan said that adulthood is the longest period after childhood and adolescence; this period is the period when a person must let go of his/her dependence on parents and start learning to be independent because he/ she already has a new task and role. Developmental tasks in early adulthood must be optimized properly because if it is not, it will be a boomerang for the individual in the future. Quarterlife crisis is a phenomenon that usually occurs in individuals between the ages of 20-30 years; this period is known as emerging adulthood. At this stage of development, individuals experience many changes and demands from their environment as a sign of the transition period from adolescence to early adulthood (emerging adulthood). The discrepancy between the ideal self and the real situation of the individual results in quarterlife crisis. In this condition the individual will feel worries, doubts, does not have a strong motivation, even fear of how the future will be. This study aims at determining the quarterlife crisis in students of the Faculty of Teacher Training and Education, University of PGRI Mahadewa Indonesia. This study is descriptive qualitative research with non-random method. The subjects in this study were the students of the Faculty of Teacher Training and Education, University of PGRI Mahadewa Indonesia aged about 20-30 years old.